Democracy after deliberation: Bridging the constitutional economicsdeliberative democracy divide - Ralston, Shane Jesse (University of Ottawa (Canada), 2007)
This dissertation addresses a debate about the proper relationship between democratic theory and institutions. The debate has been waged between two rival approaches: on the one side is an aggregative and economic theory of democracy, known as constitutional economics, and on the other side is deliberative democracy. The two sides endorse starkly different positions on the issue of what makes a democracy legitimate and stable within an institutional setting. Constitutional economists model political agents in the same way that neoclassical economists model economic agents, that is, as self-regarding, rational maximizers; so that evaluations of democratic legitimacy and stability depend on the extent to which the design of institutional rules and practices maximize individual utility by promoting efficient schemes of collective choice. Deliberative democrats, on the other hand, understand political agents as communicative reason-giving subjects who justify their preferences and positions on issues that jointly affect them in a process of consensus-directed discourse, or deliberation; so that evaluations of democratic legitimacy and order depend on the degree to which institutional norms and practices promote deliberation and draw upon deliberated public judgment. I argue that despite the numerous incompatibilities between constitutional economics and deliberative democracy---which amount to a 'deep divide'---an opportunity to produce a genuine synthesis of the two approaches arises inasmuch as it is possible to overcome several points of opposition in their separate research programmes. The central thesis of the dissertation is that it is possible to construct a bridge spanning the divide between constitutional economists and deliberative democrats, and that Dewey and Bentley's transactional view can facilitate this bridge-building project. Pursuant to this end, the points of opposition between the research programmes are mediated by way of five concepts which, on balance, favor deliberative democracy and its feasible institutionalization. In charting a transactional middle way between the two programmes, deliberative institutional designers should be empowered to achieve two objectives: (i) to integrate deliberative practices into new and existing democratic institutions and (ii) to heed the critical insights and caveats of constitutional economists, who have identified genuine limitations to realizing the deliberative ideal in modern constitutional democracies.
Keywords: Philosophy.; Political Science, General.